GENDER AND ACCENT IN THE PERCEPTION OF ENGLISH SYLLABIC CONSONANTS VS. SCHWA - Inmaculada de Jesús Arboleda Guirao; Rafael Monroy Casas (Revista de Lingüística y Lenguas Aplicadas)
This paper reports a study on the perception of English syllabic consonants vs. schwa in word final position at discourse level. Our aim is to find out whether gender and accent play a significant role in the perception of potential syllabic consonants, a topic which needs further research (see Takefuta & Black 1966; Bloom, Moore-Schoenmakers & Masataka 1999). Three females indentified a schwa/syllabic consonant in 800 words uttered in specific contextx by 80 non-rhotic native newsreaders (40m/40f) from the BBC Learning English Website. The statistical procedures used were the contingency table analysis and Kendall's correlation coefficient. The study reveals that gender and accent do not perform a significant role in the perception of this alternation. They were found not to influence the referees' perception, their degree of agreement being quite similar in the categories of each variable. The exploration of the schwa vs. syllabic consonant perception in terms of word position (within an utterance) and word emphasis is suggested.